A critical review of Gross ecosystem product accounting in China: Status quo, problems and future directions. (15th November 2022) - Hao, Chaozhi; Wu, Shuyao; Zhang, Wentao; Chen, Yuqing; Ren, Yaofa; Chen, Xin; Wang, Hao; Zhang, Linbo
Abstract: As a measure of ecosystems' contribution to human well-being, the concept of Gross Ecosystem Product (GEP) is an integrated monetary index for the evaluation of final ecosystem services, which has attracted widespread attention around the world. In China, both national and local governments have launched a series of GEP accounting pilot projects, with the aim to incorporate this new concept into real world decision-making. However, a critical review of these practices remains lacking, especially regarding their current status and problems. In this study, by performing a systematic review and data integration of current literature and government documents, we comprehensively described the GEP accounting practices in China, including pilot project's coverage, accounting methods, and policy application. Then, we identified five major problems in current GEP accounting practices in China, which prevent GEP from being accurately measured in the short term. We proposed that GEP accounting should be a constantly evolving process with both long-term and short-term improvement goals. More in detail, the accuracy issues in GEP accounting require longer periods of time to resolve; while its repeatability, comparability, and applicability should be improved in the short term, so that it can be incorporated into decision-making. In response to these challenges, we suggested the adaptation of GEP accounting index screening principles as a possible future direction, which can help to apply GEP results in the current stages of decision making. By improving GEP concept and accounting, it will be possible to establish a unified comparable GEP accounting system and reduce the gap between the GEP and decision-making. Highlights: GEP accounting has received extensive attention from the Chinese government. GEP accounting requires a co-evolution of accuracy and applicability. Five problems that prevent GEP from being accurately accounted were identified. Future GEP accounting results should be repeatable, comparable and applicable.